Luminogens for aggregation-induced emission via titanium-mediated double nucleophilic addition to 2,5-dialkynylpyridines: formation and transformation of the emitting aggregates - Foschi, Francesco; Synnatschke, Kevin; Grieger, Sebastian; Zhang, Wen-Shan; Wadepohl, Hubert; Schröder, Rasmus R.; Backes, Claudia; Gade, Lutz H. (Chemistry - a European journal, 2020)
New luminogens for aggregation-induced emission (AIE), which are characterized by a branched cross-conjugated 2,6-bis(1,2,2-triarylvinyl)pyridine motif, have been synthesized exploiting the one-pot Ti-mediated tetraarylation of 2,6-bis(arylethynyl)pyridines. Thin layer solid-state emitters were prepared by spin-coating of the luminogens, while AIE-colloidal dispersions were investigated in terms of optical density and scattering behaviour. This has given insight into particle size distributions, time evolution of the aggregation and the influence of different functionalization patterns on the luminescence of molecular aggregates. In particular, a combination of extinction spectroscopy and dynamic light scattering is being proposed as a powerful method for investigating the dynamic aggregation process in AIE-type colloids.
Version of record online: February 21, 2020
Gesehen am 26.11.2021